Experimental Study on Ferritic Stainless Steel RHS and SHS Cross-sectional Resistance Under Combined Loading. (November 2015) - Arrayago, I.; Real, E.
Abstract: The excellent corrosion resistance presented by all stainless steel grades, together with their appropriate mechanical properties, aesthetic appearance and easy maintenance, makes these metallic alloys perfect for sustainable structural performances. However, their nonlinear stress–strain behaviour, together with their strong strain hardening features, makes them different from carbon steel and makes the development of some specific guidance necessary. Although the compressive and flexural behaviour of stainless steel Rectangular and Square Hollow Sections (RHS and SHS) has been widely analysed and advanced design approaches considering strain hardening have been developed, more general loading conditions such as combined axial compression and bending moment loading conditions still need to be investigated. Within this scenario, this paper presents an experimental programme on several ferritic RHS and SHS stub column tests subjected to concentric and eccentric compression. The objective is to extend the recent research on austenitic and lean duplex stainless steel RHS under combined loading to ferritic grades by assessing the applicability and accuracy of the interaction expressions currently codified in EN1993-1-4 and those proposed in the literature. Highlights: Compression stub column tests on ferritic stainless steel RHS and SHS are presented. Combined loading stub column tests on ferritic stainless steel RHS and SHS. Design methods for cross-sectional resistance under pure compression are assessed. Class 3 limits for internal elements in compression are analysed. Different interaction expressions for combined loading are assessed.